An introduction to public enterprise in Japan - Yoshitake, Kiyohiko (Beverly Hills [Calif.] : Sage Publications, 1973)
The book contains a description of public enterprise in Japan, tracing the historical development of its present day forms and making case by case comparisons with British public enterprise. The author, tracing the history of public enterprise in Japan, theorises that the dominating influences guiding the establishment of a Japanese public enterprise sector were military and strategic in nature, whereas for Britain the motivational factors were largely democratic or socialistic.
With a foreword by William, A. Robson, London school of Economics and political science.
Bibliography: p. 334-348.
lje 18/10/18
Loans
Keywords: Government business enterprises; Public enteprises-Japan; Public enteprises-Great Britain